NUTRITIONAL AND MICROBIAL QUALITY OF HOME-MADE COMPOSITE BREAKFAST CEREALS PRODUCED IN ILARO OGUN STATE, NIGERIA - Adeosun, Florence Funke (FUDMA JOURNAL OF SCIENCES, 2026)
Breakfast cereals (BFCs) consumption is spreading and steadily replacing traditional diets due to its compositions and convenience for various consumers. This study assessed vitamins, minerals, anti-nutrients and microbial quality of BFCs produced from yellow maize, unripe plantain, soybeans and dates. These crops were processed into flours and formulated into blends of five samples at different percentages: Sample A-100% maize; Sample B-60:5:20:15; Sample C-55:10:20:15; Sample D-50:15:20:15 and Sample E-45:20:20:15. Flour blends were mixed, moist, lightly kneaded, oven dried at 80°C for 2 hours, crushed and lightly toasted. Vitamins, minerals, anti-nutrients and microbial contents of BFCs were determined using standard methods. Data were analyzed using SPSS version 20.0, with significance tested at a 5% probability level. Results revealed that Vitamins A (98.12- 121.64 µg/100g), B1 (0.17 – 0.21 mg/100), C (6.19 – 7.88 mg/100); iron (3.11 – 3.82 mg/100), zinc (0.62 – 0.79 mg/100) and potassium (701.08 - 781.44 mg/100) contents of BFCs significantly increased (P
Keywords: Breakfast cereals, Date, Micronutrients, Microbial quality